The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/gtc.12562
|View full text |Cite
|
Sign up to set email alerts
|

RBMX is a component of the centromere noncoding RNP complex involved in cohesion regulation

Abstract: Satellite I RNA, a noncoding (nc)RNA transcribed from repetitive regions in human centromeres, binds to Aurora kinase B and forms a ncRNP complex required for chromosome segregation. To examine its function in this process, we purified satellite I ncRNP complex from nuclear extracts prepared from asynchronized or mitotic (M) phase-arrested HeLa cells and then carried out LC/MS to identify proteins bound to satellite I RNA. RBMX (RNA-binding motif protein, X-linked), which was isolated from M phase-arrested cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
(76 reference statements)
1
23
0
Order By: Relevance
“…We previously found that Aurora B and RBMX interact with satellite I ncRNA at mitotic phase, indicating that satellite I ncRNA forms an RNP complex with several mitotic regulators to regulate chromosome segregation (Cho et al, ; Ideue et al, ). We used IP experiments to investigate the interaction between DHX38 and satellite I ncRNA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously found that Aurora B and RBMX interact with satellite I ncRNA at mitotic phase, indicating that satellite I ncRNA forms an RNP complex with several mitotic regulators to regulate chromosome segregation (Cho et al, ; Ideue et al, ). We used IP experiments to investigate the interaction between DHX38 and satellite I ncRNA.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that human satellite I ncRNA has a role in chromosome segregation (Ideue et al, ). Several protein factors associate with this ncRNA and function as the ncRNP complex (Cho et al, ). We found that DHX38 interacts with human satellite I ncRNA, and depletion of this protein caused defects in chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations